Integrated geostatistical and stress-field assessment of Miocene-Pleistocene strata for offshore geologic carbon storage in the Central Gulf of Mexico - Ademilola, J. A.; Pashin, Jack C. (Frontiers in Energy Research, 2025)
Opportunities for offshore geologic carbon dioxide (CO2) storage are promising, and assessment of subsurface stress is critical for minimizing the risk of CO2 leakage. This research aims to assess stress and temperature conditions to determine if the area has the ability for secure long-term storage. This objective was achieved by using a suite of geophysical well logs, four-arm caliper logs, geochemical data and data from the BOEM Sands Database for geomechanical stress fields assessment, borehole breakout analysis, and to build 3D simulations of reservoir pressure and fracture pressure in seven protraction areas of the Central Gulf of Mexico. Results of the geomechanical assessment demonstrate that well segments containing a high volume of breakouts will have low CO2 storage potential because pore pressure approaches the minimum horizontal stress. The reservoir temperature gradient in the continental slope reduces substantially beyond a depth of about ∼3,048 m (∼10,000 ft). The changing geothermal gradient appears to stem from a combination of cooling of shallow strata by the thermal mass of the water column above the mudline and conductive and advective heat flow associated with basal heat flow and active hydrocarbon generation and migration at depth. 3D models of stress reveal shelf sands ∼1,600 m (5,249 ft) below the seabed are in a safe CO2 storage window. Results indicate CO2 can be injected safely at a pressure below the minimum horizontal stress to minimize the risk of cross-formational flow, and the high porosity and permeability of sand units in this region can facilitate effective long-term storage of CO2 in mature hydrocarbon reservoirs and saline formations.